2020
DOI: 10.1039/c9pp00483a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solvent and micellar encapsulation on the photostability of avobenzone

Abstract: Avobenzone, the only UVA-absorbing molecule approved for use in sunscreens by the FDA, degrades to its diketone structure under UV light. We found that this photoisomerization is effectively prevented when avobenzone is sequestered in micelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…The tautomerisation and subsequent decrease in efficacy of irradiated avobenzone has also been demonstrated using several different comparable methods in earlier publications. [7][8][9][10][11][12][13][14] Previous studies have sought to identify ingredients that stabilise the more effective chelated enol form of avobenzone, such as compatible UV filters or antioxidants. [15][16][17] Micellar and lipid microparticle encapsulation of avobenzone have also been shown to have a role in enhancing its photostability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tautomerisation and subsequent decrease in efficacy of irradiated avobenzone has also been demonstrated using several different comparable methods in earlier publications. [7][8][9][10][11][12][13][14] Previous studies have sought to identify ingredients that stabilise the more effective chelated enol form of avobenzone, such as compatible UV filters or antioxidants. [15][16][17] Micellar and lipid microparticle encapsulation of avobenzone have also been shown to have a role in enhancing its photostability.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Micellar and lipid microparticle encapsulation of avobenzone have also been shown to have a role in enhancing its photostability. 9,18 Deuteration of the diketo methylene/enol moiety affects the tautomerisation equilibrium, by shifting it towards the ketone form. 19 Many photofragments of avobenzone have also been identified, which in turn may induce cytotoxic and skin sensitization effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Bardeen and co-workers is relevant in this context. They found that encapsulation of avobenzone into sodium dodecylsulfate micelles considerably enhances its photostability ( Hanson et al, 2020 ). This was attributed to the micelle creating an enhanced polar microenvironment, which reduces the propensity of avobenzone to diketonize and hence photodegrade.…”
Section: Discussionmentioning
confidence: 99%
“…Since the effects of UV-A radiation on the skin have been reported, the sunscreen industry and regulatory agencies now desire a broadband sunscreen (i.e., sunscreens that span across both UV-B and UV-A). However, there are still only a few Food and Drug Administration (FDA)/European Union (EU)-approved UV-A filters and the most widely used (avobenzone) is not very photostable [ 34 , 35 , 36 , 37 ]. This implies that research is still required for the identification of effective UV-A filters.…”
Section: Introductionmentioning
confidence: 99%